Assessment of Melaleuca cajuputi as heavy metals phytoremediator for sewage sludge contaminated soil - Nik Jaafar, Nik Mohd Shibli; Nik Ab. Majid, Nik Muhamad; Mohamed Shazili, Noor Azhar; Abdu, Arifin (Science Publications, 2013)
In 2011, total marine capture landings in Peninsular Malaysia decreased by 3.9% which amounted to 1,373,105 tonnes as compared to 1,428,881 tonnes in 2010. The decline is connected to marine pollution which mainly comes from land based sources. Coastal forests play an important role affecting the marine ecosystem health and need to be conserved as a buffer to minimize pollution input into marine ecosystem. Heath forest, a type of coastal forest that receives less attention compared to mangroves, also has similar role. Melaleuca cajuputi that dominates heath forest has high potential as a phytoremediator of heavy metals and also has high economic values. A greenhouse experiment was conducted to evaluate the potential of this species to extract heavy metals namely Zn and Cd from soil. Four levels of treatment were prepared where the test media was mixed with different amounts of sewage sludge (v/v) namely; T1 (control-soil only), T2 (30% sludge +70% soil), T3 (50% sludge + 50% soil) and T4 (70% sludge + 30% soil). After 90 days of experimental period, the accumulation of Zn was found to be high in the roots (137.19 mg kg-1), followed by the leaves (135.0 mg kg-1) and stems (102.24 mg kg-1). As for Cd the highest concentration was in the roots (2.05 mg kg-1), stems (1.78 mg kg-1) and leaves (1.66 mg kg-1). The species Transfer Factor (TF) values in the greenhouse experiment were > 1 but the Bio-Concentration Factor (BCF) values are≤ 1. This result shows that M. cajuputi is tolerant to Zn and Cd toxicity (low BCF) but able to transfer these elements (high TF) to the shoots for removal by leaf fall or by harvesting the shoots. In addition, the accumulation of Zn and Cd were high in the roots which suggests that Zn and Cd were efficiently immobilized (in the roots) from entering the marine ecosystem.